WORKSHOP PEMANFAATAN LIMBAH MINYAK JELANTAH MENJADI LILIN AROMATERAPI DI DESA PAMULIHAN - Ulfa, Risma Liyana; Nurzaman, Muhamad; Pratama, M Fachrul; Mayasari, Monika; Dzimar Sadli, Sep Naufal; Hasan; Fikri Khanizar, Muhamad Aqil; Daniel, Rijal; Yudha, Dimas Hendra; Safitri, Dini Oktavia; Yusrin, Iqbal Fauzi; Salma, Nazwa Mutia; Ramadhan, Rexy Surya; Sanjaya, Esa; Rianto, Raihan Lasafran; Bustamam, M. Nazry Sabiq; Burdani, Muhamad Rizky Abdilah; Nursahbani, Ripky; Maulida, Neng Nurul; Anur, Vina Delia Tri; Baihaqi, Ahmad Ghaji; Almira, Eka Apriani; Sulaeman, Agita Issa (Jurnal PkM MIFTEK, 2025)
Used cooking oil waste in Pamulihan Village has not been properly managed, resulting in water pollution and declining soil quality. This condition negatively impacts both the environment and public health. To address this problem, the KKN Group 7 of Pamulihan Village carried out a community service program. The main objective of this activity was to train residents to convert used cooking oil waste into economically valuable products—aromatherapy candles. The program included education on the dangers of waste, demonstrations of candle-making techniques, and hands-on practice sessions. This initiative addresses a key gap in Pamulihan Village, where awareness of the hazards of used cooking oil waste remains low and no practical household-level solution exists to transform it into a marketable product. The program stands out from previous efforts that may have focused solely on waste collection, as it specifically provides upcycling skills with creative economic value. As a result, residents’ understanding of the environmental risks posed by used oil waste increased significantly. They also succeeded in producing aesthetically appealing aromatherapy candles. This activity not only provides a solution to environmental problems but also opens up new economic opportunities for the community.